2014
DOI: 10.1111/jog.12495
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the differentially expressed genes and pathway cross‐talk in aggressive breast cancer

Abstract: The screened aggressive cancer-associated DEG (PTX3, SNAI2, IL-8/6, SPARC, MMP-1 and Rab25) and significant pathways (calcium signaling pathway, tyrosine metabolism, alanine, aspartate and glutamate metabolism) give us new insights into the mechanism of aggressive breast cancer cells, and these DEG may become promising target genes in the treatment of metastatic breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Apart from dysfunctional metabolism of dicarboxylates, tyrosine degradation, initiated by the tyrosine transamination with 2-oxoglutarate [ 48 - 50 ], and glutamate exchange for cystine through x c − cystine/glutamate antiporter SLC7A11 [ 51 - 54 ], are considered important for cancer cell metabolism. Stimulation of tyrosine degradation to fumarate and acetoacetate (terminal step catalyzed by FAH, Figure 6 ), with ATP-dependent acetoacetate activation to acetoacetyl-CoA by AACS (not shown in Figure 6 ), may occur due to SP-induced increase in tyrosine transamination with accumulated 2-oxoglutarate, catalyzed by TAT (Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Apart from dysfunctional metabolism of dicarboxylates, tyrosine degradation, initiated by the tyrosine transamination with 2-oxoglutarate [ 48 - 50 ], and glutamate exchange for cystine through x c − cystine/glutamate antiporter SLC7A11 [ 51 - 54 ], are considered important for cancer cell metabolism. Stimulation of tyrosine degradation to fumarate and acetoacetate (terminal step catalyzed by FAH, Figure 6 ), with ATP-dependent acetoacetate activation to acetoacetyl-CoA by AACS (not shown in Figure 6 ), may occur due to SP-induced increase in tyrosine transamination with accumulated 2-oxoglutarate, catalyzed by TAT (Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Calcium ions play a vital role in muscle contraction, neuronal transmission, cell motility, cell growth or proliferation [ 24 27 ]. It has been reported that calcium signaling pathway is related to progression and development of various cancers including lung adenocarcinoma [ 28 ], colorectal cancer [ 29 ], glioblastoma [ 30 ], breast cancer [ 31 ], and Burkitt lymphoma [ 32 ]. Calcium signaling pathway may play a key role in the progression and development of AML.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the lack of reports from CRC metabolic steadies, its dysregulation has been described in tumor tissue, peripheral blood, and urine from a variety of cancer-bearing humans and animals including gastric cancer, hepatocellular carcinoma, and myeloid leukemia [ 55 , 56 , 57 ]. This was confirmed in pathway analysis based on gene expression of aggressive breast cancer [ 58 ]. Thus, dysregulation of this pathway may represent a common metabolic profile of advanced cancer.…”
Section: Discussionmentioning
confidence: 72%